Application of The 2T 2T Method Based on Hots Literature in Learning to Write Imagination Story Text for Class VII SMPN 43 Jakarta - Edi Puryanto; Asep Supriyana; Alya Vinnisya; Muhammad Iqbal Oshmany; Audrey Sagita Purnomo; Suci Lestari; Danar Dwi Priatna; Taufik; Susi Dewi Susanti (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This study aims to describe the process and learning outcomes of the application of the two-stay- two-guest method based on HOTS literacy in the learning of imaginative story writing skills for seventh grade students of SMPN 43 Jakarta. This research was conducted in class VII SMPN 43 Jakarta with a sample of 61 people. The research method used is descriptive analysis adapted to the problem to be revealed. Based on the results of data analysis regarding the application of the 2T 2T method based on HOTS literacy in learning the ability to write imaginative story texts for class VII SMPN 43 Jakarta, it was declared successful. This can be seen from the comparison of student learning outcomes before and after being treated. The average value of the ability to write imagination text at the pretest was 55.94 and 79.76 at the posttest. From these data, it can be seen that the ability to write imaginary texts on the pretest is still lacking because it does not reach the KKM, while the ability to write imaginary texts on the posttest is categorized as good because it has reached the KKM. The success of learning the ability to write imaginative texts is strongly influenced by the 2T 2T method based on HOTS literacy.